Ovarian microcystic stromal tumor with omental metastasis: the first case report and literature review - Xiaxia Man; Zhentong Wei; Baogang Wang; Wanying Li; Lingling Tong; Liang Guo; Songling Zhang (BMC, 2021)
Abstract Background Microcystic stromal tumor (MCST) of the ovary is an extremely rare subtype of sex cord-stromal neoplasm first described by Irving and Young in 2009. Tumors from all previously reported cases (fewer than 40 total) were benign, but one was a case of ovarian MCST that reoccurred. Case presentation Herein, we present a unique single case of ovarian MCST with omental metastasis in a 47-year-old Chinese female along with its histologic and immunohistochemical profile and genetic alterations. The tumor exhibited the previously described classic microscopic features and immunoprofiles of MCST. The tumorlet in the omentum presented the same histological structures and characteristically expressed β-catenin protein (localized in the nucleus). Molecular analysis identified a point mutation (c.98C > G) in exon 3 of CTNNB1. Conclusions To the best of our knowledge, no such report has been documented for ovarian MCST with omental metastasis. The study may provide new insights into the tumor biology of MCST and provide a better understanding of this rare entity.